Evaluating Sphagnum traits in the context of resource economics and optimal partitioning theories. Issue 8 (11th May 2020) - Oke, Tobi A.; Turetsky, Merritt R.
Abstract : Tradeoffs between key aspects of plant performance such as resource acquisition and allocation underpin several trait‐based theories that have been derived for vascular plants. However, due to difficulty in quantifying traits in nonvascular plants, our theoretical understanding of how traits govern the physiological and ecological preferences of nonvascular plant species is quite limited. Here, we used the resource economics theory (RET) and optimal partitioning theory (OPT) to evaluate functional traits in mosses. We evaluated aspects of these theories in two common but ecologically different Sphagnum moss species. We used a suite of morpho‐physiological traits across a range of environmental treatments to test whether Sphagnum is capable of functional tissue partitioning and whether the two Sphagnum species studied conform to a fast or slow strategy often observed in vascular plants. Consistent with the predictions of RET, the fast‐growing species maintained a faster growth rate and low biomass across treatments. However, some of the traits responded contrary to predictions for respiration and photosynthetic rates. Consistent with OPT, Sphagnum diverted biomass from branch to capitulum to connect with the primary source of moisture when under drought stress. Overall, this study showed that moss traits could be used to test ecological theories that were developed primarily for vascular plants.